A dissimilarity index of multidimensional inequality of opportunity - Yalonetzky, G (Oxford Poverty & Human Development Initiative (OPHI), 2009)
A recent literature on inequality of opportunity offers quantitative tools for comparisons and measurement based on stochastic dominance criteria and traditional inequality indices. In this paper I suggest an additional way of assessing inequality of opportunity and operationalizing Roemer’s (1998) notion of equality of opportunity with an index of dissimilarity across distributions. The index is based on a traditional homogeneity test of multinomial distributions and is more helpful than other tools when both circumstances and advantages/outcomes are multidimensional. It also highlights the correspondence between dissimilarity in outcomes across sets of circumstances and the degree of association between circumstances and outcomes. An empirical application measures changes in inequality of opportunity from an old to a young cohort in Peru.